1990
DOI: 10.1111/j.1365-2265.1990.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like Growth Factor‐i (Igf‐i) and Igf‐i Binding Protein in the Follicular Fluids of Growth Hormone Treated Patients

Abstract: The presence of GH, insulin-like growth factor-I (IGF-I), epidermal growth factor (EGF), oestradiol (E2) and progesterone (PG) were investigated in the fluids obtained from various ovarian follicles of seven patients in whom the induction of super-ovulation was achieved only after GH (0.1 U/kg BW/day) was added to the gonadotrophin therapy. The follicular fluids of six patients responsive to treatment with gonadotrophin alone served as a control. In patients treated with combined therapy, the results demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The reduction in the amplitude and the increase in the frequency of the LH pulsatile release in normogonadotrophinaemic amenorrhoeic patients may result from the significant increase in oestradiol levels. The modulatory effect of oestrogens on amplitude and frequency of LH episodic release during the fertile life and post-menopausally have been reported by several authors (Genazzani et al, 1990a;Cagnacci et al, 1989;Filicori et al, 1986;Barreca et al, 1990;Veldhuis et al, 1984). The lack of effect of an acute infusion of G H also indicates that GH action is not direct on pituitary gonadotrophs but requires an appropriate length of time to exert its biological role on the target cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The reduction in the amplitude and the increase in the frequency of the LH pulsatile release in normogonadotrophinaemic amenorrhoeic patients may result from the significant increase in oestradiol levels. The modulatory effect of oestrogens on amplitude and frequency of LH episodic release during the fertile life and post-menopausally have been reported by several authors (Genazzani et al, 1990a;Cagnacci et al, 1989;Filicori et al, 1986;Barreca et al, 1990;Veldhuis et al, 1984). The lack of effect of an acute infusion of G H also indicates that GH action is not direct on pituitary gonadotrophs but requires an appropriate length of time to exert its biological role on the target cells.…”
Section: Discussionmentioning
confidence: 88%
“…The systemic activity of G H is probably also related to ovarian production of IGF-I. In fact, recent reports have documented increased follicular fluid IGF-I concentrations after GRF-induced G H increase as well as after GH administration (Homburg et al, 1988;Barreca et al, 1990). The absence of any significant change in the pituitary response to exogenous GnRH-induced LH release further excludes a direct involvement of the gonadotrophs in the action of GH.…”
Section: Discussionmentioning
confidence: 91%
“…The potential importance of circulating IGF-I of hepatic origin on granulosa cells in vivo is unclear. Nevertheless, Barreca et al (1990) and Owen et al (1991a) found a correlation between GH and IGF-I concentrations in the follicular fluid of women given human GH, but the source of the IGF-I (i.e. liver or granulosa cells) was unknown.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, GH secretion in fertile women varies during the menstrual cycle, exhibiting an increase at the time of ovulation (Hansen & Weeke 1974), and anovulatory women appear to be mildly GHinsufficient compared with ovulatory women (Ovesen et al 1992). Observations have indicated that the adminis¬ tration of GH to infertile patients with hyposensitive ovaries increases the response of the ovary to stimulation with gonadotrophin (Homburg et al 1988, Blumenfeld & Lunenfeld 1989, Barreca et al 1990 These studies strongly suggest that GH is important for the regulation of human ovarian function in vivo. It is not understood whether the effect of GH is mediated by a direct action on the ovary or by GH-dependent intra-or extraovarian secretion of insulin-like growth factor-I (IGF-I).…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have shown that somatomedins are synthetized by multiple human tissues where they act by paracrine and/or autocrine mechanisms of action [1][2][3][4]. Furthermore, it has recently been demonstrated that cul tured bovine adrenal fasciculata cells are able to secrete an IGF-like material.…”
Section: Introductionmentioning
confidence: 99%